2014
DOI: 10.17557/tjfc.97892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixture Ratio and Row Spacing in Hungarian Vetch (Vicia pannonica Crantz.) and Annual Ryegrass (Lolium multiflorum Lam.) Intercropping Sys

Abstract: According to the mean of 2 years, the different mixture ratios and row spacings had a statistically significant effect on all of the properties. At the end of the research, among the different mixture ratios and row spacing interactions, the highest green herbage yield (33.4 t ha -1 ), hay yield (7.5 t ha -1 ), lowest neutral detergent fiber (52.2%), and crude ash (7.8%) rates were obtained from the 60%HV+40%AR mixture and 30-cm row spacing interaction. The highest crude protein (CP) rate (17%), CP yield (1156… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
(59 reference statements)
6
9
0
Order By: Relevance
“…It was determined that the effect of the different mixtures on the RFV was significant, where the highest and lowest RFV was obtained from sole forage pea and sole triticale, respectively. (Kusvuran et al, 2014). Our findings were similar to these results.…”
Section: Resultssupporting
confidence: 93%
“…It was determined that the effect of the different mixtures on the RFV was significant, where the highest and lowest RFV was obtained from sole forage pea and sole triticale, respectively. (Kusvuran et al, 2014). Our findings were similar to these results.…”
Section: Resultssupporting
confidence: 93%
“…Sadeghpour et al (2014) reported that the mixtures of barley with annual medics had higher crude protein yield than pure crop, and it can be concluded that the tested mixture rates and pure legume are significantly different in term of protein content depending on their genetic properties. Our findings are consistent with the results of many researchers reporting that the crude protein yield increases as the ratio of legumes in the mixture increases (Vasilakoglou and Dhima, 2008;Kusvuran et al, 2014).…”
Section: Crude Protein Yield (Kg Ha -1 )supporting
confidence: 93%
“…In this study pure legume plant had lower ADF content than annual ryegrass and annual ryegrass mixtures with legume. ADF concentrations decreased as the legume proportion increased in the mixtures and similar results have also been reported by Karagic et al (2011); Sadeghpour et al (2014); Kusvuran et al (2014).…”
Section: Adf (%)supporting
confidence: 87%
See 1 more Smart Citation
“…For all these reasons, while the lowest ADF and NDF ratios were obtained from sole Hungarian vetch planting, followed by 90% Hungarian vetch + 10% Italian ryegrass mixture and they were statistically in the same group. Kusvuran et al (2014) reported similar results in Hungarian vetch and Italian ryegrass mixtures. In mixtures, LER, aggression, and competition ratio are determined to reveal the competition between plants (Dhima et al, 2007).…”
Section: Resultssupporting
confidence: 64%